Comparative study of piston mode designs for temperature-compensated surface acoustic wave resonators using SiO2/LiNbO3 structure. (1st July 2022) - Li, Yawei; Gong, Keyuan; Wong, Yu-Po; Chen, Pingjing; Wu, Zhaohui; Liang, Qi; Bao, Jing-fu; Hashimoto, Kenya
Abstract: This paper compares three different piston mode designs for temperature-compensated surface acoustic wave (TC-SAW) resonators using SiO2 /LiNbO3 structure. It was shown that in rough approximation, phase shift given by extra elements for the piston mode operation is determined by the total mass of extra elements and SiO2 which overlaid on piston region. The hammer head design without additional metal layers does not work properly due to the weaker impact of the extra elements when the SiO2 layer is thick. On the other hand, piston mode designs using metal dots or stripes are effective to suppress the transverse mode resonances even when the SiO2 layer is thick. Although larger metal thickness is preferable for the wideband operation, it also makes the split of main resonance. Thus, the optimal metal thickness can be found from this trade-off, and then the optimal metal width can be found to achieve good transverse mode suppression.